Isolation and Identification of Microorganisms in the Making of Gaplek Tannia Cocoyam (Xanthosoma sagittifolium) - Krisbianto, Oki; Purwanto, Angie Felita; Harsono, Leonardus Patrick; Budihardja, Grace Honey (Food Science and Technology Journal (Foodscitech), 2024)
Xanthosoma sagittifolium or tannia cocoyam (TC) is a root vegetable that grows in Java. Its corm can be used as flour to increase the use of TC. However, one major issue is that TC corm flour is less elastic than wheat flour. Nonetheless, modifications such as gaplek fermentation may be implemented to enhance the characteristics of TC flour. However, the microorganisms that contribute to the processing of gaplek through natural fermentation have never been characterized. This study focuses on the isolation and identification of microorganisms that play a role in the gaplek fermentation of TC. The methods used to determine these microorganisms included counting the total bacteria using Total Plate Count, identifying lactic acid bacteria using selective media De Man, Rogosa, and Sharpe Agar, as well as fungi and yeast using selective media Potato Dextrose Agar. Other tests that were conducted were motility test, catalase test, and carbohydrate fermentation test using seven different sugars, i.e., arabinose, dextrose, lactose, maltose, mannose, rhamnose, and sucrose. Sampling was conducted on dried TC chips and soaked TC chips at 0 hours and 48 hours. The results revealed the thriving of lactic acid bacteria after 48 hours of wet fermentation, which were suggested as Lactococcus and Leuconostoc. In addition to lactic acid bacteria, other microbes such as yeast and non-pathogenic Staphylococcus were also identified.